Evaluating a person-centered chronic pain service using indices of reliable and clinically significant change - Macey, Katherine; Clarke, Simon; Golijani-Moghaddam, Nima; das Nair, Roshan (European Society for Person Centered Healthcare, 2015)
Background: Psychological interventions for chronic pain often require substantial individualisation, which can undermine links with the research evidence on which treatment is based. To ensure patients receive effective therapy, evaluation is needed. This paper demonstrates the use of individual level change indices, which may be more appropriate for assessing effectiveness of person-centred treatment than traditional group-level statistics.